Long-term dietary restriction changes lipid homeostasis and consequently impairs testosterone production in aged Wistar rats - Sokanovic, Srdjan; Prvulovic, Milica; Simeunovic, Valentina; Pracer, Smilja; Mladenovic, Aleksandra (Frontiers in Nutrition, 2025)
Testosterone (T) is a central androgen responsible for the maintenance of vegetative and reproductive functions and sexual behavior in males. T is mainly synthesized through the process of testicular steroidogenesis with cholesterol (CHOL) as the initial precursor. It is known that T levels gradually decrease, along with an increase in CHOL, LDL-C, triglycerides (TG), and a decrease in HDL-C in advanced stages of life. Dietary restriction (DR) ameliorates lipid status and raises T levels in obese and overweight men. Here, we investigated whether the beneficial effects of DR on serum lipid status consequently improve T production at advanced stages; therefore, we exposed male Wistar rats to long-term DR (LTDR, 18 months). We confirmed an age-related decrease in serum T levels, reduced expression of genes and proteins of steroidogenic machinery with a simultaneous increase in serum CHOL, LDL-C, and TG levels. LTDR additionally decreased T synthesis, expression of Star/StAR and Cyp11a1/CYP11A1, and testicular CHOL levels. At the same time, LTDR reduced serum CHOL, LDL-C, and TG levels and increased HDL-C levels. To confirm that the effects of DR are determined by the duration of the treatment, we also checked the effects of the short-term DR (STDR, 3 months) and demonstrated that STDR did not alter T levels and did not affect serum lipids. Our results indicate the importance of sustained systemic lipid homeostasis for T production in advanced life stages and show that the effects of restricted food intake on testicular androgen capacity depend on the duration of DR.